BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DM - Kuntoadi, Gama Bagus; Lubis, Astri Yulia Sari; Oktavia, Liana Devi; Sendra, Eny (Ensiklopedia of Journal, 2025)
Abstract: The prevalence or incidence of Diabetes Mellitus (DM) continues to show a significant increase every year. Based on a survey conducted at Dr. M. Haulussy Hospital, data from the medical register in the last 5 years showed that the incidence of Diabetes mellitus DM has increased. The purpose of the study was to determine several factors associated with the incidence of DM. The research design used in this study was cross sectional. The research was conducted at Dr. M. Haulussy Hospital. The research was conducted in November 2023. The population in this study were all patients recorded in the medical register of Dr. M. Haulussy Hospital totaling 48 people. The research sample amounted to 48 people using total sampling. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed a relationship between the level of knowledge (p value: 0.005) and family support (p value: 0.000) on the incidence of DM. It is recommended for respondents and families to be able to increase knowledge about the importance of knowledge and family support for people with diabetes mellitus.Keywords: DM, Family Support, Knowledge.